Deletion of 2‐aminoadipic semialdehyde synthase limits metabolite accumulation in cell and mouse models for glutaric aciduria type 1. Issue 6 (26th July 2020) - Leandro, João; Dodatko, Tetyana; DeVita, Robert J.; Chen, Hongjie; Stauffer, Brandon; Yu, Chunli; Houten, Sander M.
Abstract: Glutaric aciduria type 1 (GA1) is an inborn error of lysine degradation characterized by acute encephalopathy that is caused by toxic accumulation of lysine degradation intermediates. We investigated the efficacy of substrate reduction through inhibition of 2‐aminoadipic semialdehyde synthase (AASS), an enzyme upstream of the defective glutaryl‐CoA dehydrogenase (GCDH), in a cell line and mouse model of GA1. We show that loss of AASS function in GCDH‐deficient HEK‐293 cells leads to an approximately fivefold reduction in the established GA1 clinical biomarker glutarylcarnitine. In the GA1 mouse model, deletion of Aass leads to a 4.3‐, 3.8‐, and 3.2‐fold decrease in the glutaric acid levels in urine, brain, and liver, respectively. Parallel decreases were observed in urine and brain 3‐hydroxyglutaric acid levels, and plasma, urine, and brain glutarylcarnitine levels. These in vivo data demonstrate that the saccharopine pathway is the main source of glutaric acid production in the brain and periphery of a mouse model for GA1, and support the notion that pharmacological inhibition of AASS may represent an attractive strategy to treat GA1. Abstract :